Food insecurity through the voice of adolescents participating in the Bolsa Família Program - Serenini , Milena (2023)
Objective: To understand the perception of adolescents, participants of the Bolsa Família Program (PBF), about Food Insecurity (FI). Methods: This is a study with a qualitative approach. The corpus consists of interviews with 10 adolescents and their caregivers. Results were analyzed using Content Analysis (CA) technique. Results: Four categories were established: “Hunger is not just the desire to eat”, “The ghost of hunger”, “One for all and all for one”, and “Are we safe?”. Overall, adolescents perceive the amount and variety of food changes throughout the month and that access to meat and fruits is difficult. The concern with the possibility of running out of food permeates the interviewees’ statements and intensifies among those who experienced hunger during childhood. As a result, many statements reveal the strategies developed by adolescents to alleviate FI for themselves and their families. However, statements also points to the fact that caregivers do not consider their children are truly concerned with the possibility of running out of food at home. Conclusion: Adolescents perceive food insecurity in the home and are able to respond autonomously to the situation.